Conversion of palm fatty acid distillate to bio-jet fuel-range hydrocarbons over bimetallic NiCo/SBA-15-NH2 catalyst - Derawi, Darfizzi; Azira Abdul Razak, Noor; Sakinah Saadon, Nasiha; Abdul Bar, Najihah; Taufiq-Yap, Yun Hin (Elsevier Ltd, 2025)
The study revealed a successfully production of bio-jet fuel-range hydrocarbons from PFAD via hydrogen-free and solventless deoxygenation reaction over bimetallic NiCo/SBA-15-NH2 catalyst. The NiCo/SBA-15-NH2 catalyst showed reduced surface area and pore volume (393.93 m2/g and 0.39 cm2/g), respectively after the impregnation of Ni and Co metals. The XRD and XRF analysis confirmed the presence of Ni and Co elements in the catalyst, while demonstrating that the hexagonal structure of the SBA-15 support remained intact during the wet impregnation process. The NiCo/SBA-15-NH2 catalyst also showed presence of weak and strong acid sites due to the existence of both –NH2 and Ni-Co promoters. Indeed, HRTEM analysis revealed the distribution of Ni-Co metals on the surface of the catalyst support, hence increased the catalytic active sites. Therefore, the catalytic activity for the NiCo/SBA-15-NH2 was evaluated via an optimization study at various reaction parameters, including temperature (270 ℃, 300 ℃, 315 ℃, and 330℃), catalyst loading (0, 5, and 10 wt%), and reaction time (60–360 min). The results indicated that the highest yield of hydrocarbons (C8-C20) (83 %) and bio-jet selectivity (88 %) were achieved using a 5 % catalyst loading at 330℃ for 300 min. This study provides valuable insights into the synthesis and catalytic performance of bimetallic NiCo/SBA-15-NH2 catalysts for the production of bio-jet fuel from PFAD.